Teachers’ Perception in Using Electronic Student Worksheet Liveworksheets.com as English Teaching Material at SMAN 7 Padang - Utami, Desi Tri; Addinna, Ainul (Journal of English Language Teaching, 2024)
The objective of this research is to find out the teachers’perception in using electronic student worksheets Liveworksheets.comas English teaching material at SMAN 7 Padang.The method used in this research was descriptive qualitative research. A total of 3 English teachers at SMAN 7 Padang were chosen as the participants. The purposive sampling was used to determine the participants. The data was collected through an interview. The interview guideline consisted of 13 questions about teachers’perception in using electronic student worksheets Liveworksheets.comas English teaching material. The questions were based on the four aspects of perception by Horton; attractiveness, perceived of effectiveness, relevance, and perceived motivation. The result of the data analysis showed that the teachers have a good perception in using electronic student worksheets Liveworksheets.comas English teaching material at SMAN 7 Padang even though teachers encounter multiple issues while working with electronic student worksheets Liveworksheets.com as teaching material, such as conversations about unsuitable topics, inability to download materials, and all guidelines are in English. Additional technological issues include network problems and lack of students’ internet quota, although the teacher can solve this one.The objective of this research is to find out the teachers’perception in using electronic student worksheets Liveworksheets.comas English teaching material at SMAN 7 Padang.The method used in this research was descriptive qualitative research. A total of 3 English teachers at SMAN 7 Padang were chosen as the participants. The purposive sampling was used to determine the participants. The data was collected through an interview. The interview guideline consisted of 13 questions about teachers’perception in using electronic student worksheets Liveworksheets.comas English teaching material. The questions were based on the four aspects of perception by Horton; attractiveness, perceived of effectiveness, relevance, and perceived motivation. The result of the data analysis showed that the teachers have a good perception in using electronic student worksheets Liveworksheets.comas English teaching material at SMAN 7 Padang even though teachers encounter multiple issues while working with electronic student worksheets Liveworksheets.com as teaching material, such as conversations about unsuitable topics, inability to download materials, and all guidelines are in English. Additional technological issues include network problems and lack of students’ internet quota, although the teacher can solve this one.